Some Biological Aspects of Shabbot Barbus grypus (Heckel) in Al-Hilla River/IRAQ - Hussain, N. A.; Al-Taee, M. M. S.; Al-Amari, M. J. Y. (Iraqi Journal of Aquaculture, 2022)
The present study was conducted on Shabbot Barbus grypus in Al-Hilla River/middle of Iraq. Monthly samples were collected from September 2009 to August 2010. Water temperature and transparency ranged between 12 and 37 Cº and 39 – 110 cm respectively. 132 specimens were collected. The highest number of individuals was collected in June (31) and none in January and February. The total length of individuals ranged from 95 -382 mm and wet weight varied between 7.7 and 416 gm. The length group of 180 mm was the most dominant (18.18 %) with 24 individuals. Length Weight relationship was calculated as: Log w = -1.942 + 2.889 Log L n= 132 Gonadosomatic index (GSI) values ranged between 0.06 and 3.17 for males and 0.13 and 5.33 for females. Five age groups were obtained, fishes of 1+ age group was dominant in total catch. It seems that the food nature of B. grypus in Al-Hilla River was omnivores with dominance of plant materials.